Flow of flexible matter through complex environments - Silva, Danilo (2023)
In this thesis we investigated the flow of flexible particles in complex environments, with a focus on droplet-based emulsions driven by flow and the sedimentation of deformable capsules and droplets in confined geometries. We used the lattice Boltzmann method (LBM) for fluid modelling and employed a combination of intrinsic LB methods and coupling with other techniques to simulate multicomponent droplets and flexible capsules. We conducted a comprehensive review, summarising different approaches utilising LBM in simulating fluid-filled soft structures. We highlight the relevance of these models in fields such as droplet microfluidics, drug delivery, and microparticle synthesis, while categorising the methods into fluid-structure and fluid-fluid methods, which consider interfacial boundaries and hydrodynamic interactions. We emphasise the versatility of the lattice Boltzmann method in handling complex boundary conditions and incorporating physical models. Additionally, we discussed benchmark tests for model validation. In further studies, we extended a multicomponent LB method to 3D geometries and simulated droplets flowing in a wetting channel. The results revealed a discontinuous shear thinning transition as the external force increased. We examined the effect of surface tension, directly related to droplet deformability, demonstrating that higher surface tension led to less deformable droplets and thus require larger forces for shear thinning to occur. In the next study, we looked at the shape transitions of sedimenting capsules and droplets. In the confined regime, we found a transition to bullet shape consistent with experiments. Interestingly, we find that the transition from oblate to bullet shaped droplets and capsules consistently occurs at a specific ratio between the capsule size and confinement, regardless of the flexibility. A detailed analysis of hydrodynamic stresses and forces provides valuable insights into the mechanisms driving these shape transitions. Overall, the application of the lattice Boltzmann method, and the combination of computational and experimental approaches (conducted by the Oppenheimer Group for Soft Matter Physics at Tel Aviv University), sheds light into the dynamics of droplet-based systems and deformable capsules. These findings have implications for a wide range of fields involving soft matter systems, opening up new possibilities for designing and optimising processes in droplet microfluidics, drug delivery, food & cosmetic industry and beyond.